2014
DOI: 10.1371/journal.pone.0111713
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Coagulation Factor XI Expression by MicroRNAs in the Human Liver

Abstract: High levels of factor XI (FXI) increase the risk of thromboembolic disease. However, the genetic and environmental factors regulating FXI expression are still largely unknown. The aim of our study was to evaluate the regulation of FXI by microRNAs (miRNAs) in the human liver. In silico prediction yielded four miRNA candidates that might regulate FXI expression. HepG2 cells were transfected with miR-181a-5p, miR-23a-3p, miR-16-5p and miR-195-5p. We used mir-494, which was not predicted to bind to F11, as a nega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 43 publications
1
24
0
Order By: Relevance
“…DDG scores assigned by PITA to binding of candidate miR-NAs encompassing the studied variant are shown in Table 1; miR-26a-5p, miR-26b-5p and miR-1297 were predicted to target only to the F8 3 0 UTR containing the G allele. Moreover, a recent study that performed expression arrays including 1898 human mature miR-NAs using total RNA of healthy human liver samples (FVIII is synthesized in the liver) found miR-26a-5p and miR-26b-5p as highly expressed miRNAs in hepatocytes (Table S1) [7]. Since the coexpression of a miRNA and its target is necessary for a miRNA effect, this expression data in hepatic tissue reinforce the functional relevance of our in silico findings.…”
supporting
confidence: 86%
See 1 more Smart Citation
“…DDG scores assigned by PITA to binding of candidate miR-NAs encompassing the studied variant are shown in Table 1; miR-26a-5p, miR-26b-5p and miR-1297 were predicted to target only to the F8 3 0 UTR containing the G allele. Moreover, a recent study that performed expression arrays including 1898 human mature miR-NAs using total RNA of healthy human liver samples (FVIII is synthesized in the liver) found miR-26a-5p and miR-26b-5p as highly expressed miRNAs in hepatocytes (Table S1) [7]. Since the coexpression of a miRNA and its target is necessary for a miRNA effect, this expression data in hepatic tissue reinforce the functional relevance of our in silico findings.…”
supporting
confidence: 86%
“…Significant differences in bold. ¶ MiRNA arrays (n = 4) using Sanger miRBase Release 18.0 and 19.0 as previously described [7]. Median of sample signal expressed in arbitrary units.…”
mentioning
confidence: 99%
“…miRNA expression has been detected in anucleate platelets [24,25], exosomes [26], and microparticles [27] possessing procoagulant properties. Moreover, recent reports have demonstrated that miRNAs directly regulate hemostatic proteins, such as protein S, antithrombin, tissue factor, fibrinogen, PAI-1, and FXI [21,[28][29][30][31][32]. Collectively, these studies suggest that miRNAs play a role in haemostasis and could contribute to the pathogenesis of thrombotic disorders.…”
Section: Discussionmentioning
confidence: 87%
“…MiRNAs are small non-coding conserved RNAs of about 22 nucleotides, which predominantly bind to the 3 0 untranslated region (UTR) of target genes (Bartel, 2009). Recent in vitro studies demonstrated that plasminogen-activator inhibitor-1 (PAI-1), fibrinogen, tissue factor and factor XI may be regulated by miRNAs, thereby supporting their role in regulating levels of haemostatic factors (Fort et al, 2010;Teruel et al, 2011;Marchand et al, 2012;Salloum-Asfar et al, 2014;Teruel-Montoya et al, 2015). Recent in vitro studies demonstrated that plasminogen-activator inhibitor-1 (PAI-1), fibrinogen, tissue factor and factor XI may be regulated by miRNAs, thereby supporting their role in regulating levels of haemostatic factors (Fort et al, 2010;Teruel et al, 2011;Marchand et al, 2012;Salloum-Asfar et al, 2014;Teruel-Montoya et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…They mostly lower gene expression by decreasing mRNA translation or increasing mRNA degradation. Recent in vitro studies demonstrated that plasminogen-activator inhibitor-1 (PAI-1), fibrinogen, tissue factor and factor XI may be regulated by miRNAs, thereby supporting their role in regulating levels of haemostatic factors (Fort et al, 2010;Teruel et al, 2011;Marchand et al, 2012;Salloum-Asfar et al, 2014;Teruel-Montoya et al, 2015). As genetic variations in the miRNA binding site of a target gene can affect the effect of miRNAs on protein regulation (Mishra et al, 2008), we set out to study the association between miRNA target site variants in coagulation genes and venous thrombosis.…”
Section: Discussionmentioning
confidence: 99%